Constant BCR-ABL transcript level >or=0.1% (IS) in patients with CML responding to imatinib with complete cytogenetic remission may indicate mutation analysis - Poláková, Katerina Machová; Polívková, Václava; Rulcová, Jana; Klamová, Hana; Jurcek, Tomás; Dvoráková, Dana; Zácková, Daniela; Pospísil, Zdenek; Mayer, Jirí; Moravcová, Jana (Experimental hematology, 2010)
OBJECTIVE: Of 140 chronic myeloid leukemia patients responding to imatinib with complete cytogenetic remission, 32 exhibited a plateau of BCR-ABL values at >or=0.1% level in a minimum of three subsequent samples (minimal duration, 6 - 9 months). Median follow-up of unchanged BCR-ABL transcript level was 12 months (range, 6 - 64). We tested this group of patient for BCR-ABL mutations to reveal resistance development and to evaluate the risk of disease progression. MATERIALS AND METHODS: Altogether, 134 samples of peripheral blood of these 32 patients were tested for mutation in BCR-ABL kinase domain. RESULTS: Mutation was detected by direct sequencing in 9 of 32 patients (28%). Loss of complete cytogenetic remission or 1 log rise of BCR-ABL was observed in five of nine patients at a median of 5 months (range, 4-17) since first detection of mutation. One patient with no mutation relapsed 12 months after the start of the BCR-ABL plateau. In 5 of 32 patients without mutation (16%), BCR-ABL level significantly decreased after the first plateau to levels that stayed unchanged for a median of 11 months (range, 7-28). CONCLUSION: We show here that the BCR-ABL constant levels >or=0.1% (BCR-ABL plateau) in imatinib-responding patients may indicate mutation analysis. This approach highly reduces the number of examinations for mutation in chronic myeloid leukemia responders and may present cost-effective alternative applicable in clinical practice.
Keywords: mutace; dospělí; Female; pyrimidiny; Adult; ženské pohlaví; piperaziny; cytogenetické vyšetření; Reproducibility of Results; bcr-abl fúzní proteiny; lidé; chronická myeloidní leukemie; Antineoplastic Agents; protinádorové látky; Cytogenetic Analysis; messenger RNA; Mutation; RNA, Messenger; reprodukovatelnost výsledků; Benzamides; Remission Induction; imatinib mesylát; Male; Aged; benzamidy; Piperazines; indukce remise; lidé středního věku; senioři; mužské pohlaví; Leukemia, Myelogenous, Chronic, BCR-ABL Positive; Fusion Proteins, bcr-abl; Middle Aged; Imatinib Mesylate; Pyrimidines; Humans